Les enjeux entre le marché éditorial et la condition de la littérature au Québec - Bujnowska, Ewelina (Polskie Towarzystwo Badań Kanadyjskich, 2013)
Canada and Quebec are concerned about supporting national publishing industry, which – given the small size of the market – could not survive without government assistance. The funding is provided by the Canada Council for the Arts, the Society for Development of Cultural Enterprises (SODEC) and Canadian Heritage through such programs as the Canada Book Fund (CBF), formerly called the Program of Assistance to Book Publishers, and the Program of Support for Cultural Exportation and Influence (Sodexport). It is important to reflect on the impact of these programs on the Quebec publishing industry today and understand the scope of renewal that is experienced by new publishing houses based in Quebec, mainly Montreal.